Economic Growth in Latin America and the Caribbean : Stylized Facts, Explanations, and Forecasts - Loayza, Norman; Fajnzylber, Pablo; Calderón, César (Washington, DC: World Bank, 2012)
Economic Growth in Latin America and the Caribbean analyzes whether economic reforms have been beneficial to growth in the region. In doing so, it recognizes that growth is driven by a variety of factors - in some cases poor growth is due to insufficient structural reforms (e.g., low trade openness), in others to inappropriate stabilization policies (e.g., exchange rate overvaluation), and still in others to negative international conditions (e.g., growth slowdown in industrial countries). It is obvious but still correct to say that identifying the problem is the first step towards the solution. This book contributes to this effort by examining the growth performance of countries in Latin America and the Caribbean, explaining the underlying sources of their economic growth, and designing a strategy for further growth.